2017
DOI: 10.1371/journal.pone.0184777
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pentavalent antimoniate intralesional infiltration therapy for cutaneous leishmaniasis: A systematic review

Abstract: BackgroundThe mainstays of cutaneous leishmaniasis (CL) treatment, in several world regions, are pentavalent antimony (Sbv) compounds administered parenterally, despite their recognized toxicity, which requires frequent laboratory monitoring and complicates their use in areas with scarce infrastructure. As result of these drawbacks, the WHO Expert Committee on leishmaniasis has expanded the recommendations for the use of local therapies, including Sbv intralesional infiltration (IL-Sbv), as CL therapy alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 51 publications
(81 reference statements)
4
76
1
2
Order By: Relevance
“…Such a difference might be due to duration and numbers of applications i.e 12 weeks of application vs. 6 weeks and 6-8 times, application technique (using cotton tipped vs. cryo gun) and size of lesions. But to the contrary our result is relatively low when compared to trials in Egypt (100%) [16], This might be due to application of cryotherapy for undetermined times, till all lesions are cleared. In addition, other groups containing 26 patients had a combined cryotherapy and IL SSG therapy with a cure rate of 96.1%.…”
Section: Discussioncontrasting
confidence: 92%
“…Such a difference might be due to duration and numbers of applications i.e 12 weeks of application vs. 6 weeks and 6-8 times, application technique (using cotton tipped vs. cryo gun) and size of lesions. But to the contrary our result is relatively low when compared to trials in Egypt (100%) [16], This might be due to application of cryotherapy for undetermined times, till all lesions are cleared. In addition, other groups containing 26 patients had a combined cryotherapy and IL SSG therapy with a cure rate of 96.1%.…”
Section: Discussioncontrasting
confidence: 92%
“…In 2013, the Pan American Health Organization Expert Committee on leishmaniasis also included this approach in regional guidelines restricted to reference centres and to single lesions not involving the face or joints . Recently, a systematic review confirmed a global efficacy of 75% for pentavalent antimony intralesional therapy, a similar cure rate to that described in the New World for parenteral antimony treatment . It is important to note that this is an off‐label route of a drug that has been used for decades, but was only just incorporated into the Brazil's public health system officially, with expanding large‐scale use.…”
Section: Introductionmentioning
confidence: 70%
“…The patients were treated with MA – Glucantime ® – ampoules of 81 mg/ml, using the same lot control number (528240), produced by Sanofi‐Aventis Pharma and assigned by the Brazilian Ministry of Health. Patients were submitted to weekly intralesional infiltration using a standardised and previously validated technique . According to the study protocol, a maximum of eight infiltrations was performed deeply in the dermis and in the adjunctive subcutaneous tissue aiming to achieve saturation of the lesion, defined as swelling of the entire lesion accompanied or not by pallor.…”
Section: Methodsmentioning
confidence: 99%
“…8 Available data on the feasibility of local therapies in the Americas is limited. 9,11,13 A previous study in our center showed modest applicability of local therapies to pediatric populations (26% and 53% were eligible, based on PAHO and WHO criteria, respectively). 14 Children constitute a population with special needs for therapy but represent only around 11% of Colombian cases.…”
Section: Introductionmentioning
confidence: 81%
“…3,6 To address these issues, in 2010 the World Health Organization (WHO) issued recommendations for the use of local therapies as alternatives for treating CL. 8 These therapies include intralesional antileishmanials (antimony and pentamidine), 9,10 physical therapies (cryotherapy and thermotherapy), 11 and topical drugs (e.g., paramomycin). 5 The WHO recommendations aim to reduce toxicity and increase adherence, given the better risk-benefit ratio of local therapies compared with systemic drugs for CL, especially for mild clinical presentations.…”
Section: Introductionmentioning
confidence: 99%